Conformal piezoelectric systems for clinical and experimental characterization of soft tissue biomechanics - Dagdeviren, Canan; Shi, Yan; Joe, Pauline; Ghaffari, Roozbeh; Balooch, Guive; Usgaonkar, Karan; Gur, Onur; Tran, Phat L.; Crosby, Jessi R.; Meyer, Marcin; Su, Yewang; Chad Webb, R.; et al. (Nature materials, 2015)
Mechanical assessment of soft biological tissues and organs has broad relevance in clinical diagnosis and treatment of disease. Existing characterization methods are invasive, lack microscale spatial resolution, and are tailored only for specific regions of the body under quasi-static conditions. Here, we develop conformal and piezoelectric devices that enable in vivo measurements of soft tissue viscoelasticity in the near-surface regions of the epidermis. These systems achieve conformal contact with the underlying complex topography and texture of the targeted skin, as well as other organ surfaces, under both quasi-static and dynamic conditions. Experimental and theoretical characterization of the responses of piezoelectric actuator–sensor pairs laminated on a variety of soft biological tissues and organ systems in animal models provide information on the operation of the devices. Studies on human subjects establish the clinical significance of these devices for rapid and non-invasive characterization of skin mechanical properties. Piezoelectric sensors and actuators are embedded in pliable devices that conform to human skin and organ surfaces. These devices enable rapid characterization of the mechanical properties of soft tissues under various clinical conditions.